Pengembangan Media Digital Berbasis QR Code Pada Folklor: Kawah Putih Sebagai Pembelajaran Sastra di Sekolah Dasar - Aljamaliah, S. Nailul Muna (ppjbsip, 2022)
The development of the times requires everyone to understand the sophistication of technology. In the 21st century, everything digital has become the main foundation in the development of digital media. Digital media is one of the media that can be used in the learning process. In the process of learning literature, especially in elementary school, it can adjust to the needs. Folklore can be used as teaching material in the process of learning literature. The purpose of this research is to develop QR Code-based digital media on folklore as a medium that can be used in the learning process. The method used in this research is the ADDIE method in which there are 4 stages in the research process and data collection namely Analysis, Design, Development, Implementation, and Evaluation. The analysis phase is carried out to determine the needs related to the problems and characteristics of students in implementing the learning process. At the design stage, digital media design is carried out to be developed. After designing digital media, it is then developed and validated by experts. Based on the results of the recapitulation of the eligibility value of the media, an average value of 3.63 was obtained from validator 1, 3.75 from validator 2. The total average value of the validator was 3.69 or equivalent to 92%. Based on the average feasibility value, it can be concluded that the media is very suitable for use in the process of learning literature in elementary school.AbstrakPerkembangan zaman menuntut setiap orang memahami kecanggihan teknologi. Pada abad 21 yang serba digital menjadi landasan utama dalam pengembangan media digital. Media digital menjadi salah satu media yang dapat digunakan pada proses pembelajaran. Dalam proses pembelajaran sastra khususnya di SD dapat menyesuaikan dengan kebutuhan. Folklor dapat dijadikan sebagai materi ajar dalam proses pembelajaran sastra. Tujuan dari penelitian ini adalah mengembangkan media digital berbasis QR Code pada cerita rakyat sebagai media yang dapat digunakan pada proses pembelajaran. Metode yang digunakan pada penelitian ini adalah metode ADDIE yang mana ada 4 tahapan dalam proses penelitian dan pengumpulan data yaitu Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi. Tahap analisis dilakukan untuk mengetahui kebutuhan yang berkaitan dengan permasalahan dan karakteristik siswa dalam pelaksanaan proses pembelajaran. Pada tahap desain dilakukan perancangan media digital yang akan dikembangkan. Setelah dirancang media digital kemudian dikembangkan dan divalidasi oleh ahli. Berdasarkan hasil rekapitulasi nilai kelayakan media diperoleh nilai rata-rata 3,63 dari validator 1, 3,75 dari validator 2. Jumlah rata-rata keseluruhan nilai dari validator sebesar 3,69 atau setara dengan 92%. Berdasarkan nilai rata-rata kelayakan dapat disimpulkan bahwa media sangat layak digunakan pada proses pembelajaran sastra di SD.